2017
DOI: 10.1007/s13312-018-1226-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Face-to-Face Education on Anxiety and Pain in Children with Minor Extremity Injuries Undergoing Outpatient Suturing in Emergency Department

Abstract: Objective To assess the effect of face-to-face education on anxiety and pain in children with minor extremity injuries undergoing outpatient suturing. Methods Children in intervention and control groups received face-to-face education (10 minutes) and no specific education, respectively. The anxiety and pain was measured using Modified-Yale Preoperative Anxiety Scale, and pain by Faces Pain Scale–Revised, respectively in 3 stages viz, pre-procedure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, their study confirmed that procedures involving the removal of percutaneous bone pins do indeed generate moderate pain in children (3.03/10 SD 2.69). As suggested by other studies, removal of sutures related to a fracture or injury in children generates moderate to severe pain (4.9/10 SD 3.1) (Bigdeli Shamloo et al., 2018). On the other hand, administration of narcotics or procedural sedation for bone pins and/or suture removal probably exceeds the real need for most patients, and it can take up to 60 min to reach a peak analgesic effect.…”
Section: Introductionmentioning
confidence: 84%
“…However, their study confirmed that procedures involving the removal of percutaneous bone pins do indeed generate moderate pain in children (3.03/10 SD 2.69). As suggested by other studies, removal of sutures related to a fracture or injury in children generates moderate to severe pain (4.9/10 SD 3.1) (Bigdeli Shamloo et al., 2018). On the other hand, administration of narcotics or procedural sedation for bone pins and/or suture removal probably exceeds the real need for most patients, and it can take up to 60 min to reach a peak analgesic effect.…”
Section: Introductionmentioning
confidence: 84%
“…Studies state that beliefs and values, as cultural dimensions and results of life experience, can play a fundamental role in the onset, severity, and persistence of anxiety [ 26 , 27 ]. The study by Bigdеli Shamloo and colleagues (2018) shows that in-person visit rеducеs anxiеty in surgical candidatеs [ 27 ]. Thе diffеrеncе bеtwееn thеir study and thе prеsеnt rеsеarch is in thе mеthod.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have demonstrated its effectiveness [39][40][41], questions persist regarding the optimal methods for delivering patient education. Some experts advocate for the use of phone, written materials, or video resources [42,43], while other research suggests that direct personal interaction and verbal communication significantly alleviate anxiety symptoms [44,45]. Additionally, modern technologies, including mobile applications [46], online resources [47], and even virtual reality tools [48], have proven effective in managing anxious patients.…”
Section: Management Of Preoperative Anxietymentioning
confidence: 99%